Application of microalgae Scenedesmus acuminatus enhances water quality in rice-crayfish culture - Yuan, Danni; Wang, Lan; Wang, Hongxia; Miao, Rongli; Wang, Yulu; Jin, Hu; Tan, Lu; Wei, Chaojun; Hu, Qiang; Gong, Yingchun (Frontiers in Bioengineering and Biotechnology, 2023)
Improper management of aquatic environments substantially restricts the development of the aquaculture industry. The industrialisation of the crayfish Procambarus clarkii, for example, is currently being limited by poor water quality. Research suggests that microalgal biotechnology has a great potential for water quality regulation. However, the ecological effects of microalgal applications on aquatic communities in aquaculture systems remain largely unknown. In the present study, 5 L Scenedesmus acuminatus GT-2 culture (biomass 120 g L-1) was added to an approximately 1000 m2 rice-crayfish culture to examine the response of aquatic ecosystems to microalgal application. The total nitrogen content decreased significantly as a result of microalgal addition. Moreover, the microalgal addition changed the bacterial community structure directionally and produced more nitrate reducing and aerobic bacteria. The effect of microalgal addition on plankton community structure was not obvious, except for a significant difference in Spirogyra growth which was inhibited by 81.0% under microalgal addition. Furthermore, the network of microorganisms in culture systems with the added microalga had higher interconnectivity and was more complex, which indicating microalgal application enhance the stability of aquaculture systems. The application of microalgae was found to have the greatest effect on the 6th day of the experiment, as supported by both environmental and biological evidence. These findings can provide valuable guidance for the practical application of microalgae in aquaculture systems.